2016
DOI: 10.4236/jtr.2016.41007
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Evaluation of GeneXpert MTB/RIF Assay for the Detection of Rifampicin Resistant <i>Mycobacterium tuberculosis</i> among Pulmonary Tuberculosis Patients in Bangladesh

Abstract: Background: The emergence of multidrug resistant tuberculosis (MDR-TB) and extensively drugresistant tuberculosis (XDR-TB) has highlighted the need for early accurate detection and drug susceptibility. Objective: The purpose of the present study was to evaluate the accuracy of GeneXpert MTB/RIF assay for the detection of Mycobacterium tuberculosis and rifampicin resistance. Methodology: This cross sectional study was done in the Department of Microbiology at Sir Salimullah Medical College, Dhaka and National I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Although the primary objective of this study was not to validate rapid molecular testing against the reference standard method, we compared the rate of RR-TB detected using GeneXpert MTB/RIF Assay with BD BACTEC TM MGIT TM 960 SIRE liquid culture system for automated drug susceptibility testing. The sensitivity of 100% of GeneXpert MTB/RIF Assay in detecting rifampicin resistance in our study was in line with previous studies reported by Meawed TE et al, (100%; [62] in Egypt, Jahan H et al, (98.5%; 2016) [63] in Bangladesh, Pandey P et al, (98.6%; 2017) [64] in Nepal and Mekkaoui L et al, (100%; 2021) [65] in Belgium; but higher than the sensitivity reported in previous studies by Tang T et al, (84.0%; 2017) [66] in China and Feliciano CS et al, (94%; 2019) [67] in Brazil. Whereas, the specificity of 94.6% of GeneXpert MTB/RIF Assay in detecting rifampicin resistance in our study was lower than previous study reported by Meawed TE et al, (100%; [62] in Egypt, Jahan H et al, (100%; 2016) [63] in Bangladesh, Pandey P et al, (100%; 2017) [64] in Nepal, Mekkaoui L et al, (99.2%; 2021) [65] in Belgium and Feliciano CS et al, (98%; 2019) [67] in Brazil; but higher than the specificity reported by Tang T et al, (87.8%; 2017) [66] in China.…”
Section: Discussionsupporting
confidence: 92%
“…Although the primary objective of this study was not to validate rapid molecular testing against the reference standard method, we compared the rate of RR-TB detected using GeneXpert MTB/RIF Assay with BD BACTEC TM MGIT TM 960 SIRE liquid culture system for automated drug susceptibility testing. The sensitivity of 100% of GeneXpert MTB/RIF Assay in detecting rifampicin resistance in our study was in line with previous studies reported by Meawed TE et al, (100%; [62] in Egypt, Jahan H et al, (98.5%; 2016) [63] in Bangladesh, Pandey P et al, (98.6%; 2017) [64] in Nepal and Mekkaoui L et al, (100%; 2021) [65] in Belgium; but higher than the sensitivity reported in previous studies by Tang T et al, (84.0%; 2017) [66] in China and Feliciano CS et al, (94%; 2019) [67] in Brazil. Whereas, the specificity of 94.6% of GeneXpert MTB/RIF Assay in detecting rifampicin resistance in our study was lower than previous study reported by Meawed TE et al, (100%; [62] in Egypt, Jahan H et al, (100%; 2016) [63] in Bangladesh, Pandey P et al, (100%; 2017) [64] in Nepal, Mekkaoui L et al, (99.2%; 2021) [65] in Belgium and Feliciano CS et al, (98%; 2019) [67] in Brazil; but higher than the specificity reported by Tang T et al, (87.8%; 2017) [66] in China.…”
Section: Discussionsupporting
confidence: 92%
“…It is worth noting that the study by Kateete et al, (2019) that reported a 50% and 30% rate of MDR and XDR respectively, analyzed only samples that had been deemed as drug resistance 55 hence may not necessarily reflect the actual prevalence at the community level. While much progress has been made in the recent past to understand the drug resistance situation in sub-Saharan Africa 47 , 95 – 98 , adequate data is still lacking due to weak surveillance and diagnostic capabilities 40 . For instance, rifampicin and isoniazid resistance is well monitored and described in most countries, either through continuous surveillance or periodic surveys unlike resistance to ethambutol and Pyrazinamide (PZA), the other two first-line drugs, which are not routinely monitored and thus poorly described 99 .…”
Section: Discussionmentioning
confidence: 99%
“…While much progress has been made in the recent past to understand the drug resistance situation in sub-Saharan Africa 47,[95][96][97][98] , adequate data is still lacking due to weak surveillance and diagnostic capabilities 40 . For instance, rifampicin and isoniazid resistance is well monitored and described in most countries, either through continuous surveillance or periodic surveys unlike resistance to ethambutol and Pyrazinamide (PZA), the other two first-line drugs, which are not routinely monitored and thus poorly described 99 .…”
Section: Mycobacterium Tuberculosis Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…As an alternate, recent molecular diagnostic techniques are increasingly being promoted owing to their rapid turn around time and high sensitivity and specificity (5). The World Health Organization (WHO) has endorsed the implementation of GeneXpert MTB/RIF assay for national tuberculosis programsi n developing countries (10). The Xpert MTB/RIF (Cepheid Inc.) is an automated, user friendly and rapid test based on nested realtime PCR assay and molecular beacon technology for MTB detection and RIF resistance.…”
Section: Introductionmentioning
confidence: 99%